Strategi Literasi Budaya dan Kewargaan Melalui Peningkatan Variasi Sumber Belajar di Desa Budaya Bangunjiwo - Setyawati, Adella Puspa; Aulia, Syifa Siti (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2023)
AbstractCultural and civic literacy is very important in the era of globalization to maintain the local culture that becomes the identity of the nation. However, cultural and civic literacy is considered less competitive and studies are still minimal in its development. Bangunjiwo Village as a cultural village status is one example of the implementation of cultural and civic literacy. The type of research used is qualitative which uses data as material for analysis and is the narrative and descriptive approach. Data collection of observations, interviews, and documentation then triangulate techniques. The results of research on cultural and civic literacy strategies through increasing the variety of quality learning resources are as follows: 1) Access to library reading with facilities. 2) Digital media as a learning resource using websites, youtube, and instagram, 3) Site visits and history with traditional ceremonial activities and new ways of conveying historical stories through dances such as Ambangunjiwo Goa Wurung historical traces from Prince Diponegoro, 4) Traditional games and art exercises by means of children's dolanan festivals become unique events in conveying the diversity of traditional games packaged into dances. 5) Translation of supporting materials through spatial naming using Javanese script.—————————AbstrakLiterasi budaya dan kewargaan sangat penting untuk menghadapi era globalisasi untuk menjaga budaya lokal yang menjadi identitas bangsa. Akan tetapi, literasi budaya dan kewargaan dianggap kurang kompetitif serta kajian yang masih minim dalam pengembangannya. Desa Bangunjiwo sebagai status desa budaya menjadi salah satu contoh dalam implementasi literasi budaya dan kewargaan. Jenis penelitian yang digunakan adalah kualitatif yang menggunakan data sebagai bahan analisis dan bersifat naratif dan pendekatan deskriptif. Pengumpulan data cara observasi, wawancara, dan dokumentasi kemudian melakukan triangulasi teknik. Hasil penelitian strategi literasi budaya dan kewargaan melalui peningkatan variasi ragam sumber belajar bermutu, sebagai berikut: 1) Akses bacaan perpustakaan dengan fasilitas. 2) Media digital sebagai sumber belajar menggunakan website, youtube, dan instagram, 3) Kunjungan situs dan sejarah dengan kegiatan upacara adat dan cara baru menyampaikan kisah sejarah melalui tarian seperti Ambangunjiwo Goa Wurung jejak sejarah dari Pangeran Diponegoro, 4) Permainan tradisional dan latihan seni dengan cara festival dolanan anak menjadi acara yang unik dalam menyampaikan keberagaman permainan tradisional dikemas menjadi tarian. 5) Penerjemahan bahan penunjang melalui cara penamaan tata ruang menggunakan aksara jawa.